Realtà in frantumi. Il paesaggio, l’io e la storia in ’Conglomerati’ di Andrea Zanzotto - Cappelluzzo, Adriana (Incontri. Rivista europea di studi italiani, 2016)
Fragments of reality: landscape, self and history in Conglomerati by Andrea Zanzotto Reflection on the landscape is a constant in the poetry of Andrea Zanzotto and can also be observed in his last masterpiece, Conglomerati. The surrounding world crumbles into many little fragments within which the lyric “self” keeps moving in order to find a poetic Word that might grasp the truth of existence. Zanzotto’s final collection reveals an interest in the coordinated illustration of the numerous and demeaning implications of landscape, self and history, as well as poetry’s function as a form of resistance to decay. This analysis focuses on the poems in Conglomerati that touch on these themes, whilst also referring to Zanzotto’s other masterpieces and the baseline of his poetics. The examination of a selection of these poems gradually reveals the sense of self, landscape, poetry, and history assumed in the collection as a whole. The attention of the poet is entirely focused on grasping the dramatic transformation that has indelibly altered the landscape of North-East Italy: a violent and illegal urbanization permanently threatens the Edenic force of those mountains where once upon a time the lyric “self” experimented in self-knowledge. The landscape is ruined, history is in decay. Nevertheless, this human history, crushed in a crumbling landscape, still preserves the poetic word and the need to pronounce it. In the context of the destruction of everything and everyone, poetry remains a mirage of truth and strength.